Parent satisfaction when schools from home during the COVID-19 pandemic - Nur Alvira; Tri Baskoro Tunggul Satoto (Intelektual Pustaka Media Utama, 2022)
The COVID-19 crisis has forced education systems around the world to look for alternatives to face-to-face teaching with learning from home. This kind of education system has never existed before in Indonesia. This condition raises parental concerns and dissatisfaction with learning outcomes and children's achievements, resulting in suboptimal parental support. This study aimed to examine the factors related to the level of satisfaction and the role of parents in providing support during the child's learning process from home. This study employed a cross-sectional design involving 130 parents who have children attending the Klaten District State Elementary School, Indonesia. The sampling technique was using proportional simple random sampling. Data were analyzed using simple and multiple logistic regression tests with type one error rates=5%. The results showed that the determinant factor influencing parental dissatisfaction was their perception of the lack of teacher support during the implementation of the home learning system. The low education of parents, their low perception of the learning system from home, and the decreased value of children’s knowledge affect parent satisfaction when schools from home (SFH). These factors contributed 65.42% affect parental support in assisting children when studying during pandemic COVID-19.